Presidential Address: the Declining Significance of the Literature Review in Criminal Justice Scholarship: Towards a New Paradigm - Maddan, Sean (American journal of criminal justice, 2018)
Literature reviews in criminological and criminal justice journal articles have long served as an integral component in our empirical backyard. In this address I explore the value of the literature review in peer-reviewed research articles. I begin by evaluating the merits of the literature review section in empirically refereed research articles. I propose abandoning the literature review, due to its overall insignificance and best practices from other disciplines. Based on reasons outlined in this speech, I elaborate on the strengths and weaknesses of this somewhat controversial notion in the criminological/criminal justice discipline.